The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2010 14th IEEE International Enterprise Distributed Object Computing Conference 2010
DOI: 10.1109/edoc.2010.23
|View full text |Cite
|
Sign up to set email alerts
|

Supporting Change Propagation in the Evolution of Enterprise Architectures

Abstract: Enterprise Architecture (EA) models the whole vision of an organisation in various aspects regarding both business processes and information technology resources. As the organisation grows, tbe architecture governing its systems and processes must also evolve to meet with the demands of the business environment. In this context, a critical issue is change propagation: given a set of primary changes that have been made to the EA model, what additional secondary changes are needed to maintain consistency across … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
16
0

Year Published

2010
2010
2020
2020

Publication Types

Select...
3
3
3

Relationship

3
6

Authors

Journals

citations
Cited by 17 publications
(16 citation statements)
references
References 11 publications
(10 reference statements)
0
16
0
Order By: Relevance
“…Previous work has shown the effectiveness of this framework in supporting change propagation within agentoriented design models [11], [12], [13], [14]. Our recent work [15] has also indicated that the framework is applicable to deal with changes in enterprise architectures.…”
Section: Introductionmentioning
confidence: 90%
“…Previous work has shown the effectiveness of this framework in supporting change propagation within agentoriented design models [11], [12], [13], [14]. Our recent work [15] has also indicated that the framework is applicable to deal with changes in enterprise architectures.…”
Section: Introductionmentioning
confidence: 90%
“…After the reconciliation step additional changes can be inferred using change propagation techniques (cf. [12], [13]). In step 5, the model is then populated again with this inferred knowledge.…”
Section: Integration Subprocessmentioning
confidence: 95%
“…Dam et al 54 propose an enterprise architectural (EA) description language for change propagation within an EA model. To resolve conflicts and inconsistency while propagating the changes, the framework devises repair plans based on consistency and well-formedness rules formulated in Alloy.…”
Section: Conflict Detection and Resolutionmentioning
confidence: 99%